2014
DOI: 10.1684/abc.2014.0970
|View full text |Cite
|
Sign up to set email alerts
|

A rare pediatric case of cutaneous gamma/delta T-cell lymphoma

Abstract: Cutaneous ␥/␦ T-cell lymphoma (CGD-TCL) is a recent entity described in the newly revised World health organization-European organization for research and treatment of cancer classification of cutaneous lymphomas. Only a few cases have been reported, of which two pediatric cases. A 15 years old child with a 6 months history of polyadenopathy, cutaneous lesions, general edema and deterioration of general condition was hospitalized. Results from laboratory testing, cutaneous histopathology and immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This extraordinary rare disorder has been reported in children, but it is basically an adult condition. 4,[119][120][121][122][123][124] Merrill et al 125 reported the occurrence of primary cutaneous gd T-cell lymphoma (CGDTCL) in 3 individuals before the age of 25 years, including a 1-year-old child. The lesions are usually found on the extremities and trunk.…”
Section: Primary Cutaneous T-cell Lymphomamentioning
confidence: 99%
“…This extraordinary rare disorder has been reported in children, but it is basically an adult condition. 4,[119][120][121][122][123][124] Merrill et al 125 reported the occurrence of primary cutaneous gd T-cell lymphoma (CGDTCL) in 3 individuals before the age of 25 years, including a 1-year-old child. The lesions are usually found on the extremities and trunk.…”
Section: Primary Cutaneous T-cell Lymphomamentioning
confidence: 99%
“…Primary CGD‐TCL is exceedingly rare in children; several pediatric cases reports are described in the literature . Some children with CGD‐TCL were included in the series of Toro et al.…”
Section: Cutaneous T‐cell Lymphomasmentioning
confidence: 99%
“…Therapy for CGD‐TCL is not well established, and treatment guidelines are mostly based on anecdotal reports. Most reported cases have been managed with doxorubicin‐based regimens or SMILE (dexamethasone, methotrexate, ifosfamide, l ‐asparaginase, and etoposide), whereas ASCT or allogeneic SCT has been mostly used in cases of progressive disease in adults . Half of CGD‐TCL patients treated with first‐line CHOP initially respond to treatment, but early disease progression followed by death is the usual outcome for most adult patients .…”
Section: Cutaneous T‐cell Lymphomasmentioning
confidence: 99%
“…Primary cutaneous gamma delta T cell lymphoma (PCGDTCL) was previously classified with SPTCL, but it is now considered a separate entity in the 2008 WHO classification (Swerdlow et al , ) based on the expression of TCR γδ and worse prognosis (Willemze et al , ). It mostly occurs in adults, but paediatric cases have been reported (Kerbout et al , ). Patients present with patch, plaque or tumour lesions in the extremities.…”
Section: Primary Cutaneous Gamma Delta T Cell Lymphomamentioning
confidence: 99%